The Review of Tax Context Related to Tourism: การทบทวนบริบทด้านภาษีที่เกี่ยวข้องกับการท่องเที่ยว - Untong, Akarapong; Kantawongwarn, Kansinee; Wichian, Anyarat (Journal of Applied Economics and Management Strategy, 2020)
บทคัดย่อ บทความนี้มีวัตถุประสงค์เพื่อนำเสนอบริบทด้านภาษีที่เกี่ยวข้องกับการท่องเที่ยว โดยทบทวนและสังเคราะห์งานศึกษาเกี่ยวกับภาษีท่องเที่ยวทั้งในระดับนานาชาติและระดับประเทศ เพื่อสร้างความเข้าใจเบื้องต้นเกี่ยวกับโครงสร้างและระบบภาษีที่เกี่ยวข้องกับการท่องเที่ยว ซึ่งจะเป็นประโยชน์ต่อการศึกษาผลกระทบจากการเก็บและ/ ลดหย่อนภาษีที่เกี่ยวข้องกับการท่องเที่ยว รวมทั้งการศึกษาเพื่อหาแนวทางการจัดเก็บภาษี ค่าธรรมเนียม และค่าบริการพิเศษที่เกี่ยวข้องกับกิจกรรมการท่องเที่ยวในอนาคต ภาษีเกี่ยวกับการท่องเที่ยวอาจอยู่ในรูปของค่าธรรมเนียม ค่าบริการพิเศษ หรือภาษีทางอ้อม ซึ่งแบ่งเป็นภาษีทั่วไปและภาษีเฉพาะที่ขึ้นอยู่กับมูลค่าของทรัพย์สินหรือกำหนดเป็นจำนวนเงินคงที่สำหรับสินค้าหรือบริการที่ขายแต่ละหน่วย โดยมีการเรียกเก็บทั้งจากภาคธุรกิจและนักท่องเที่ยว เพื่อเพิ่มรายได้ให้กับภาครัฐ เรียกคืนต้นทุนการให้บริการสาธารณะ และทำให้ต้นทุนภายนอกถูกรวมในราคาที่นักท่องเที่ยวจ่าย รวมทั้งมาตรการจูงใจทางภาษีเพื่อกระตุ้น สนับสนุน และส่งเสริมการท่องเที่ยว ที่ผ่านมามีการศึกษาผลของการเก็บภาษีการท่องเที่ยวใน 2 ลักษณะ ได้แก่ 1) การศึกษาผลกระทบของการเก็บภาษี และ 2) การศึกษาเกี่ยวกับภาระภาษี การกระจายภาระภาษี และการส่งออกภาระภาษี สำหรับประเทศไทยมีรายการภาษีที่เกี่ยวข้องกับการท่องเที่ยวหลายรายการทั้งที่อยู่ในรูปของภาษีทั่วไปและภาษีเฉพาะ รวมทั้งมาตรการให้สิทธิประโยชน์ทางภาษี ซึ่งเกือบทั้งหมดเป็นนโยบายระดับชาติ แต่การศึกษาผลของการเก็บภาษีการท่องเที่ยวยังมีน้อย โดยเฉพาะในระดับท้องถิ่น ทำให้องค์กรปกครองส่วนท้องถิ่นบางแห่งที่มีแหล่งท่องเที่ยวที่มีชื่อเสียงต้องแบกรับภาระต้นทุนในการดูแลนักท่องเที่ยว สิ่งแวดล้อม ทรัพยากรธรรมชาติ รวมทั้งสาธารณูปโภคต่างๆ ที่สนับสนุนการท่องเที่ยวในท้องถิ่น คำสำคัญ: นโยบายภาษี การท่องเที่ยว ภาษีการท่องเที่ยว ABSTRACT This article aims to present the context of taxes related to tourism by reviewing and synthesizing the studies of tourism taxes, both internationally and nationally, in order to provide a basic understanding of the structures and systems of tax related to tourism. Studying the impact of imposing and/or reducing tax related to tourism is useful, including study to find ways to collect taxes, fees, and special service fees related to tourism activities in the future. Tourism taxes may be in the form of fees, special service fees, or indirect taxes, which are divided into general taxes or specific taxes and are based on the value of the property or as a fixed amount for each product or service sold. These tourism taxes may be collected from both the business sector and tourists in order to increase revenue for the government, to compensate the cost of public services, and to make the external costs included with the price that tourists paid. In the past, the studies on the effect of tourism taxation exhibited two characteristics: 1) studying the effect of tax collection and 2) studying the tax burden, tax distribution, and the export of the tax burden. For Thailand, there are many tourism-related taxes, both in the form of general taxes and specific taxes, including tax incentive measures that are almost entirely a national policy. However, in Thailand there has still been no study on the effect of tourism taxation, especially at the localized level. In addition, many local government organizations that have famous tourist sites to have to bear the cost of looking after tourists, the environment, and natural resources, including various utilities that support local tourism. Keywords: Tax Policy, Tourism, Tourism Tax